Who’s Afraid of the Fenians? The Fenian Scare on Prince Edward Island, 1865-1867 - Macdonald, Edward (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2009)
Abstract In the winter of 1866 Prince Edward Island was swept by rumours of an attack by the Fenian Brotherhood, Irish American rebels intent on using an invasion of British North America to loosen Britain’s hold on Ireland. Unlike other parts of British North America, the handling of the Fenian Scare on Prince Edward Island had much less to do with Confederation than the local government’s ongoing campaign to suppress the Tenant League, a radical land reform movement, and its manipulation of sectarian discord for electoral gain – thus illustrating how transnational issues mutate through interaction with local issues.